2019
DOI: 10.1177/1457496919874484
|View full text |Cite
|
Sign up to set email alerts
|

Primary small intestinal neuroendocrine tumors are highly prevalent and often multiple before metastatic disease develops

Abstract: Background: Small intestinal neuroendocrine tumors are the most common of small bowel malignancies with a clinical incidence of about 1 per 100,000 persons per year. There has been a threefold increase in the incidence of small intestinal neuroendocrine tumor during later decades, but there are no studies that clarify whether this is due to a true higher incidence or if the rise is a mere product of, for instance, improved diagnostic modalities. The aim of this study was to investigate the incidence of clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…A comprehensive Swedish autopsy study comparing post-mortem to real-time diagnosis over a time period showed a high number of undiagnosed NEN in the small bowel. 18 A Canadian study showed that, despite overall increased NEN incidence, the proportion of those presenting with metastatic disease had decreased significantly, with earlier stage at diagnosis, and posited increased detection as the cause. 8 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A comprehensive Swedish autopsy study comparing post-mortem to real-time diagnosis over a time period showed a high number of undiagnosed NEN in the small bowel. 18 A Canadian study showed that, despite overall increased NEN incidence, the proportion of those presenting with metastatic disease had decreased significantly, with earlier stage at diagnosis, and posited increased detection as the cause. 8 …”
Section: Introductionmentioning
confidence: 99%
“… 19 Diagnosing NEN at an earlier stage improves prognosis, and may be important in screening for other solid organ cancers. 18 …”
Section: Introductionmentioning
confidence: 99%
“…Small intestinal neuroendocrine neoplasms (SI-NEN) are the most common small bowel tumours with an annual incidence of about 0.5-1.05/100.000/year in Western countries. [1][2][3] The primary tumours are often small, but they spread early to lymph nodes and the liver. 4 About 60% of patients have distant metastases at the time of diagnosis, mostly in the liver.…”
Section: Introductionmentioning
confidence: 99%
“…This hypothesis is particularly valid for NETs, which are often described as potentially indolent tumours. Studies from Malmö County during 1958–1982, with an autopsy frequency reaching 87 per cent of all deceased persons found an extremely high incidence of 53 small intestinal NETs per million person-years 14 , 15 . The vast majority of these patients had been asymptomatic.…”
Section: Discussionmentioning
confidence: 99%